THE EFFECT OF X-RADIATION ON THE OXYGEN UPTAKE OF EMBRYONATE EGGS - Greiff, Donald (The Rockefeller University Press, 1953)
Groups of 10 day old embryonate eggs were given 250, 500, 750, and 1000 r of x-radiation, and oxygen consumption determinations were made subsequently at various intervals during a period of 90 hours. In general, the effect of radiation was moderately stimulatory, but after 90 hours the respiratory rates of the 250 and 1000 r groups were well below those of the control groups. The most striking effect, noted in 3 separate experiments, was the occurrence of a "3 step staircase" type of oxygen consumption curve in all irradiated groups, the levelling off periods apparently occurring between the 4th and 14th, the 24th and 36th, and the 42nd and 66th hours after exposure. These curves were in striking contrast to those shown by groups of non-irradiated eggs, which were practically of the straight line type.